Soccer on Sunday - Osborne, Mary Pope.; Murdocca, Sal (New York : A Stepping Stone Book, Random House, 2014)
Jack and Annie search for the fourth secret of greatness for Merlin the Magician in Mexico City at the 1970 World Cup Games. They hope to learn something new from soccer player great, Pele.
A Merlin Mission.
4.2
3-6
570L
N
Keywords: d; d; Magic -- Fiction; Time travel -- Fiction; Brothers and sisters -- Fiction; Soccer -- Fiction; Fantasy; Siblings -- Fiction; Fantasy fiction; Soccer -- Fiction; Mexico -- History -- 1946-1970 -- Fiction; Mexico -- History -- Fiction; Soccer stories; Fantasy fiction